Hukum Keluarga dalam Masyarakat Multikultural: Tinjauan Sosiologis atas Keberagaman Sistem Hukum di Indonesia - Fauzul Kabir (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT The relationship between family law and Indonesian society is dynamic and complex due to the coexistence of three legal systems: Islamic law, customary law, and colonial civil law. This diversity creates tensions between religious values, local traditions, and the demands of modernity, often triggering conflicts as well as accommodations. This paper aims to analyze the dynamics of interactions between family legal systems and identify forms of conflict and inequality in access to justice in Indonesia's plural society. This research is library research, employing a socio-legal approach along with structural functionalism theory and Luhmann's legal system theory. The data were obtained through document studies of laws, the Compilation of Islamic Law (KHI), court decisions, books, and journals. The analysis was conducted using a qualitative, descriptive-analytical approach. The findings show that people tend to negotiate between legal systems pragmatically, choosing the system that is most beneficial or aligns with their values. The interaction between legal systems takes three main forms: accommodation, negotiation, and open conflict. However, inequality of access to justice remains a serious challenge, especially for lower-class communities who prefer to resolve disputes through customary means or religious leaders due to complicated and expensive court procedures. In conclusion, family law in Indonesia must be understood as a living and ever-changing social reality, not merely as statutory texts. An adaptive and accommodative approach that favors vulnerable groups is needed to realize social justice amidst diversity. Keywords: family law, legal pluralism, social dynamics